2015
DOI: 10.1002/lsm.22444
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐fractional, directional skin tightening: A porcine model

Abstract: Significant minimally invasive skin tightening in a preferred direction can be achieved by removing skin with coring needles followed by wound closure. The direction of shrinkage is influenced by the direction of micro-hole closure, irrespective of the skin tension lines. This approach may allow reshaping the skin in a desired direction without scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…As with excision‐and‐lift operations, the direction of closure could be used to affect the direction of skin tightening. In our previous study with tightening by coring needles , we found that the direction of shrinkage could be influenced by the direction of the applied compressive dressing. Our data in this study show a trend toward the directed closure, but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…As with excision‐and‐lift operations, the direction of closure could be used to affect the direction of skin tightening. In our previous study with tightening by coring needles , we found that the direction of shrinkage could be influenced by the direction of the applied compressive dressing. Our data in this study show a trend toward the directed closure, but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
“…In a previous performed study , we demonstrated that primary closure of a fractional array of small full‐thickness skin wounds made with coring needles could produce significant skin contraction without scarring. That previous study showed that removing 10% of the skin by coring needles combined with immediate closure using an adherent wound dressing applied postoperatively for 7 days yielded an 8% reduction of skin area after 28 days.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…At present, the minipigs are becoming the most commonly used large laboratory animals because the minipigs are small in body size, easy to operate, and share anatomical, physiological and biochemical similarities with humans. Because of the remarkable similarities between porcine and human skin structure, pigs are often considered as an ideal model for skin-related studies, including skin grafting [ 1 ], cosmetic identification [ 2 ], ultraviolet radiation [ 3 ], skin cancer [ 4 ], burns [ 5 , 6 ], frostbite [ 7 ], skin aging [ 8 ] and etc. However, because of pig skin coated with shaggy hairs, shaving hair process is inevitable before skin test or surgery.…”
Section: Introductionmentioning
confidence: 99%